Analysis of Cancerous Tissue Temperature in the Breast During Hyperthermia - (:unkn) unknown (IEEE, 2017)
In this paper, the computational modeling of the 2D human breast in hyperthermia treatment at 2.45 GHz is studied. The mathematical tool used in this study for investigating the distribution of generated heat is the COMSOL software where the breast is modeled by Pennes' bioheat equation. The model simulation is conducted to investigate the effects of exposure time and power inputs on the cancerous tissue temperature field. The results show that this method can cure the breast cancer patient without damaging the breast tissue.
Keywords: Breast cancer; Ilyperthermia; COMSOL Multiphysics; Electromagnetic wave; Bioheat transfer